Treatment of adrenal metastases with conventional or hypofractionated image-guided radiation therapy: patterns and outcomes - Bürgy, Daniel; Rabe, Leonie; Siebenlist, Kerstin; Stieler, Florian; Fleckenstein, Jens; Giordano, Frank Anton; Wenz, Frederik; Boda-Heggemann, Judit (Anticancer research, 2018)
Background/Aim: Metastases involving the adrenal glands can be treated surgically or with radiation therapy. Retrospective studies indicate that radiotherapy for this indication is safe, well-tolerated and associated with symptom palliation and good local control. We conducted this analysis to report on patterns and outcomes of patients with adrenal metastases treated with hypo- or conventionally fractionated image-guided radiotherapy. Patients and Methods: Patients with adrenal metastases from solid tumors treated at our department between 01/2010-12/2017 were reviewed. A total of 22 lesions were treated in 18 patients with a median dose of 35 Gy (20-60 Gy) in a median number of 7 (4-25) fractions. Results: No grade ≥3 toxicity occurred. Median overall survival was 11.9 months. Five local failures occurred (22.7%). Lesion sizes or radiation dose were not correlated with local control. Patients treated for oligometastatic and oligoprogressive disease had a median overall survival of 33 and 6.5 months, respectively (palliative/polymetastatic: 1.6 months). Symptoms improved in all patients treated for clinically apparent lesions. Conclusion: Stereotactic radiotherapy of adrenal metastases was safe and effective in patients with oligometastases or oligoprogression. In palliative patients, short-course radiotherapy complemented with supportive care should be preferred.
Gesehen am 24.10.2019